1, 3-Disulfoimidazolium chloronickellate immobilized HZSM-5 framework as visible-light-induced heterogeneous photocatalyst for advanced oxidation process. (12th February 2018) - Saikia, Susmita; Gogoi, Pinky; Borah, Ruli
Abstract : Hybrid photocatalysts of [Dsim]2 [NiCl4 ]/HZSM-5 were prepared by wet impregnation and their application is demonstrated as feasible heterogeneous photocatalysts for oxidative degradation of methylene blue under sunlight. Abstract : Ionic solid 1, 3-disulfoimidazolium chloronickellate [Dsim]2 [NiCl4 ] with low band gap value can be modified as a heterogeneous photocatalyst after immobilization on siliceous zeoliteHZSM-5 . In this study, different percentages of [Dsim]2 [NiCl4 ]/HZSM-5 supported ionic systems were prepared as acidic solid materials via wet impregnation. The structural changes of the parentHZSM-5 framework within the heterogenized materials were studied using IR, UV, SEM-EDX, PXRD, Raman, BET, TGA, Hammett acidity, HRTEM and ICP-OES techniques. Assessment of their thermal and water tolerance and intensity of photoluminescence spectra instigate the hybrid samples as possible heterogeneous photocatalysts for oxidative degradation of model dye compound methylene blue (MB) involving H2 O2 and sunlight at ambient temperature in aqueous solution. This study may contribute to a new perception for the exploration of halometallate ionic salt systems as potential visible light driven photocatalysts in organic transformation.